Automated analysis of atrial late gadolinium enhancement imaging that correlates with endocardial voltage and clinical outcomes: A 2-center study - Malcolme-Lawes, L. C.; Juli, C.; Karim, Rashed; Bai, Wenjia; Quest, Rebecca; Lim, P. B.; Jamil-Copley, S.; Kojodjojo, Pipin; Ariff, B.; Davies, D. W.; Rueckert, Daniel; Francis, D. P.; et al. (Heart Rhythm, 2013)
Background For late gadolinium enhancement (LGE) cardiovascular magnetic resonance (CMR) assessment of atrial scar to guide management and targeting of ablation in atrial fibrillation (AF), an objective, reproducible method of identifying atrial scar is required. Objective To describe an automated method for operator-independent quantification of LGE that correlates with colocated endocardial voltage and clinical outcomes. Methods LGE CMR imaging was performed at 2 centers, before and 3 months after pulmonary vein isolation for paroxysmal AF (n = 50). A left atrial (LA) surface scar map was constructed by using automated software, expressing intensity as multiples of standard deviation (SD) above blood pool mean. Twenty-one patients underwent endocardial voltage mapping at the time of pulmonary vein isolation (11 were redo procedures). Scar maps and voltage maps were spatially registered to the same magnetic resonance angiography (MRA) segmentation. Results The LGE levels of 3, 4, and 5SDs above blood pool mean were associated with progressively lower bipolar voltages compared to the preceding enhancement level (0.85 ± 0.33, 0.50 ± 0.22, and 0.38 ± 0.28 mV; P =.002, P <.001, and P =.048, respectively). The proportion of atrial surface area classified as scar (ie, >3 SD above blood pool mean) on preablation scans was greater in patients with postablation AF recurrence than those without recurrence (6.6% ± 6.7% vs 3.5% ± 3.0%, P =.032). The LA volume >102 mL was associated with a significantly greater proportion of LA scar (6.4% ± 5.9% vs 3.4% ± 2.2%; P =.007). Conclusions LA scar quantified automatically by a simple objective method correlates with colocated endocardial voltage. Greater preablation scar is associated with LA dilatation and AF recurrence. © 2013 Heart Rhythm Society. All rights reserved.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Atrial fibrillation; Delayed-enhancement magnetic resonance imaging; Radiofrequency ablation